Swine backyard production systems in central chile: characterizing farm structure, animal management, and production value chain - Baumberger, Cecilia; Di Pillo, Francisca; Galdames, Pablo; Oyarzún, Cristóbal; Marambio, Víctor; Jiménez Bluhm, Pedro.; Hamilton West, Christopher. (MDPI, 2023)
Backyard production systems (BPS) are highly distributed in central Chile. While poultry BPS have been extensively characterized, there remains a notable gap in the characterization of swine BPS in central Chile. In addition, there is evidence that zoonotic pathogens, such as influenza A virus and Salmonella spp., are circulating in backyard poultry and pigs. A total of 358 BPS located in central Chile were evaluated between 2013 and 2015 by interviewing farm owners. Severe deficiencies in biosecurity measures were observed. The value chain of swine backyard production identified food, veterinary care (visits and products), and replacement or breeding animals as the primary inputs to the backyard. The most common origin of swine replacements was from outside the BPS (63%). The main outputs of the system were identified as meat and live animals, including piglets and breeding animals. In 16% of BPS, breeding animals were lent to other BPS, indicating the existence of animals and animal product movement in and out of backyard farms. Results from this study indicate that swine BPS in central Chile represents an animal–human interface that demands special attention for implementing targeted preventive measures to prevent the introduction and spread of animal pathogens and the emergence of zoonotic pathogens.
Keywords: Backyard; Value chain; Cerdos